Validasi Teorema Geometri pada kasus Titik Berat Segitiga secara Induktif Menggunakan Komputasi Simbolik - Vicky Julius Mawuntu (Jurnal FisTa : Fisika dan Terapannya, 2023)
Symbolic computing emphasizes the exact processing of data representations. The exact representative states that even though the output is small, the data generated using processing can produce larger mathematical expressions. To overcome this problem, a method needs to be used in representing data. This process is carried out to solve a physical problem in the case of the center of gravity on a triangle. Symbolic programming languages can convert rational numbers, so that this symbolic processing can be applied to inductively validate geometric theorems in the case of triangular center.